2010
DOI: 10.1111/j.1365-246x.2010.04856.x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for 3-D joint inversion of MT, gravity and seismic refraction data

Abstract: S U M M A R YWe present a 3-D joint inversion framework for seismic, magnetotelluric (MT) and scalar and tensorial gravity data. Using large-scale optimization methods, parallel forward solvers and a flexible implementation in terms of model parametrization allows us to investigate different coupling approaches for the various physical parameters involved in the joint inversion. Here we compare two different coupling approaches, direct parameter coupling where we calculate conductivities and densities from sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(171 citation statements)
references
References 54 publications
1
143
0
2
Order By: Relevance
“…Further improvements in models of mineral deposits can be obtained by including resistivity borehole logs as local prior information (e.g., Yan et al 2017a), by transferring structural boundaries observed in reflection seismic images or seismic velocity models to 2D or 3D inversion models of MT data (e.g., Le et al 2016b;Yan et al 2017b;Moorkamp 2017) or by performing joint inversions of MT, seismic and potential field data using petrophysical or structural coupling (e.g., Moorkamp et al 2011;Gallardo and Meju 2011;Haber and Gazit 2013;Takam Takougang et al 2015;Moorkamp 2017). Strictly speaking, well logs only represent the resistivity structure up to a few metres off the borehole and may be affected by borehole fluids and the invaded zone around the borehole.…”
Section: Resultsmentioning
confidence: 99%
“…Further improvements in models of mineral deposits can be obtained by including resistivity borehole logs as local prior information (e.g., Yan et al 2017a), by transferring structural boundaries observed in reflection seismic images or seismic velocity models to 2D or 3D inversion models of MT data (e.g., Le et al 2016b;Yan et al 2017b;Moorkamp 2017) or by performing joint inversions of MT, seismic and potential field data using petrophysical or structural coupling (e.g., Moorkamp et al 2011;Gallardo and Meju 2011;Haber and Gazit 2013;Takam Takougang et al 2015;Moorkamp 2017). Strictly speaking, well logs only represent the resistivity structure up to a few metres off the borehole and may be affected by borehole fluids and the invaded zone around the borehole.…”
Section: Resultsmentioning
confidence: 99%
“…As is noted in Roberts et al (2012), the simulators, particularly the seismic simulator (Heincke et al, 2006), are more sophisticated than required for the problem at hand; however, to facilitate future development and allow integration and direct comparison with other work (Heincke et al, 2006;Moorkamp et al, 2011Moorkamp et al, , 2013, we use these simulators.…”
Section: Methods and Model Spacementioning
confidence: 99%
“…Similarly, there are also conceptual intricacies associated with properly and quantitatively including most kinds of uncertainty associated with the problem, for example, uncertainty in the data measurements and model discrepancy (due to the fact that a model is not a complete representation of nature). Recently however, a few authors such as Roy et al (2005), Heincke et al (2006), and Moorkamp et al (2011Moorkamp et al ( , 2013) make considerable progress in developing structural coupling-based joint inversion methodologies through crossgradient and other coupling schemes. Bodin et al (2012) also develop hierarchical Bayes approaches for joint inversion.…”
Section: Joint Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, and enhance formation-fluid tracking (Rector III 1995;Hoversten et al 2003;MacGregor et al 2007;Chen et al 2007;Hu et al 2009;Newman et al 2010;Moorkamp et al 2011;Abubakar et al 2012;Gao et al 2012;Lien 2013).…”
Section: Introductionunclassified